Controlling the properties of radiation-synthesized thermoresponsive oligoether methacrylate hydrogels by varying the monomer side-chain length; self-composite network containing crystalline phase. (15th August 2018) - Piechocki, Krzysztof; Kozanecki, Marcin; Kadlubowski, Slawomir; Pacholczyk-Sienicka, Barbara; Ulanski, Piotr; Biela, Tadeusz
Abstract: A series of thermo-responsive hydrogels have been synthesized by radiation-induced crosslinking polymerization in bulk based on; oligoether methacrylates (OEGMAs) of side chain lengths of 2–19 EG; monomer units. Side chain lengths have been shown to have a pronounced effect on synthesis parameters (monomers of longer side chains are more easily crosslinked, and the inert atmosphere promotes crosslinking more than air) and hydrogel properties (the thermal stability of obtained networks and their swelling capacities, as well as the temperature of Volume Phase Transition (VPT), increase with increasing oligoether side group length, while the VPT becomes less narrow). Networks based on oligoether methacrylates of sufficiently long side chains (over 7 monomer units) are capable of partial crystallization, forming self-composites, and the crystalline phase is chemically linked to a continuous, coherent polymer network. Graphical abstract: Image 1 Highlights: PMEOnMAs networks was synthesized by radiation-induced crosslinking polymerization. Side group of PMEOnMAs determines properties and applicability of the products. PMEOnMAs with n ≤ 7 form thermo-responsive hydrogels. Swelling degree and volume phase transition temperature increase with n. Networks of PMEOnMAs with n ≥ 7 are capable of partial crystallization.